1991
DOI: 10.1177/026921559100500409
|View full text |Cite
|
Sign up to set email alerts
|

Review articles : Pressure sores: methods used for the assessment of patient support surfaces

Abstract: In the seriously ill, the paralysed and the elderly patient, many factors such as poor skin blood flow, malnutrition and immobility predispose to a high incidence of decubitus ulcers or pressure sores. The development of a sore is a complex process, but skin distortion and localized pressure are considered important precipitating factors. Over the last two decades manufacturers have produced a large variety of support surfaces claiming to be effective in prevention as well as treatment of sores. However, a rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The area with the highest-pressure value was the GA, with 12.70 and 12.55 mmHg in the NLs and CLs, respectively, which were lower than the blood flow-based threshold of 30 mmHg and the perception-based threshold of 17 mmHg reported in previous studies. [32][33][34][37][38][39][40]…”
Section: Difference In the Clothing Pressure Between The Normal And C...mentioning
confidence: 99%
“…The area with the highest-pressure value was the GA, with 12.70 and 12.55 mmHg in the NLs and CLs, respectively, which were lower than the blood flow-based threshold of 30 mmHg and the perception-based threshold of 17 mmHg reported in previous studies. [32][33][34][37][38][39][40]…”
Section: Difference In the Clothing Pressure Between The Normal And C...mentioning
confidence: 99%
“…The patient had been considered high risk for PU development using a Waterlow score assessment (Waterlow, ; Wellard and Lo, ) on admission to ICU. For many patients, this would indicate supplying a pressure relieving air filled mattress in order to reduce PU risk, as basic hospital mattresses have minimal pressure relieving properties (Rithalia and Kenney, ). However, an air mattress cannot provide accurate spinal alignment and thus would have negative clinical implications for spinal injured patients (Ferrell et al ., ), therefore this was not a clinical option.…”
Section: Nursing Challengesmentioning
confidence: 99%
“…Curiously though, one issue that has not been addressed, and one in which no national consensus exists, is the optimal time cycle. Although it has been suggested that an optimal time cycle in sleeping healthy volunteers should be at 5-minute intervals (Rithalia, 1991), no data exists that suggest that this is of any benefit to the critically ill. The time cycle and inflation pressures of the cells are of extreme importance as it can have tremendous impact on tissue interface pressures.…”
Section: Preventionmentioning
confidence: 99%